Brunei’s silent claims in the South China Sea: a case for the theory of trade expectations - Bama Andika Putra (Cogent Social Sciences, 2024)
Although many Southeast Asian countries have asserted maritime claims in the South China Sea, often in conflict with China’s claims, Brunei has adopted a different stance. Brunei continues to display a stance of being a silent claimant to the South China Sea despite the growing turbulence of the disputed waters in recent years with the continued reclamations and use of maritime constabulary forces. In comprehending this irregularity, this article employs Copeland’s ‘theory of trade expectation’ and classifies the South China Sea as a grey zone conflict, which leads to the following conclusions: 1) Brunei is displaying deference to China’s South China Sea claims due to the growing convergence of Brunei’s long-term economic plans to China’s introduction of the Belt Road Initiative, and 2) A visibly apparent, growing economic interdependence of Brunei towards Chinese trade deals and foreign investments, as seen in the past decade of China’s involvement in Brunei’s infrastructural development, petrochemical facilities, joint oil, and gas explorations, and the establishment of the Brunei-Guangxi Economic Corridor. The Sultanate’s recent scramble to diversify its economy has led it to embrace a desperate attempt to secure opportunities from China by steadily neglecting its claims in the South China Sea.